2017
DOI: 10.1111/and.12881
|View full text |Cite
|
Sign up to set email alerts
|

Semen quality and infertility status can be identified through measures of oxidation-reduction potential

Abstract: Standard analyses for evaluating semen quality require technical expertise and are interpretive in nature. Oxidative stress (OS) alters many of the semen parameters; thus, a measure of OS could be an indicator of semen quality. Static oxidation-reduction potential (sORP) is a universal measure of OS traditionally used in environmental applications but is increasingly used in biomedical studies. sORP was measured to determine how well it associates with semen quality and if it differentiates semen from infertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 26 publications
4
43
0
Order By: Relevance
“…These findings were corroborated by a study we published the following year in which a static ORP cut-off value of 1.38 mV/10 6 sperm/mL was determined via ROC curve analysis to differentiate normal from abnormal semen samples within a sample of 365 infertile men (Fig. 6), suggesting that ORP could be a valuable addition to SA as a useful marker of semen quality [56].…”
Section: Validation Of Oxidation-reduction Potential As An Indicator supporting
confidence: 58%
See 1 more Smart Citation
“…These findings were corroborated by a study we published the following year in which a static ORP cut-off value of 1.38 mV/10 6 sperm/mL was determined via ROC curve analysis to differentiate normal from abnormal semen samples within a sample of 365 infertile men (Fig. 6), suggesting that ORP could be a valuable addition to SA as a useful marker of semen quality [56].…”
Section: Validation Of Oxidation-reduction Potential As An Indicator supporting
confidence: 58%
“…*Significant at p<0.05. Adapted from the article of Arafa et al (Andrologia 2018;50)[56] with original copyright holder's permission.…”
mentioning
confidence: 99%
“…It is specifically calibrated to detect human sperm at 0.1–400 mV. Requiring only 30 µL of sample volume and less than 5 minutes for the entire procedure, the MiOXSYS System yields an ORP value with a high sensitivity, specificity, and accuracy [ 53 54 55 56 57 58 ]. Fresh or frozen semen and seminal plasma can be also be evaluated [ 59 ].…”
Section: Measurement Of Oxidation-reduction Potential: Principle Of Tmentioning
confidence: 99%
“…sORP provides a composite measure of available oxidants and reductants whereas cORP denotes the amount of accessible reductants to combat OS. Due to more promising data, sORP became the topic of interest and was mostly referred to as “ORP” in later studies [ 54 55 56 58 ]. All studies were conducted with at least a power of 80% with statistical significance set at p<0.05.…”
Section: Clinical Significance Of Oxidation-reduction Potential Measumentioning
confidence: 99%
“…Various studies have investigated the potential diagnostic role of ORP measurement in male infertility assessment (Agarwal, Sharma, Roychoudhury, Plessis, & Sabanegh, ; Arafa et al, ; Roychoudhury et al, ). Studies on infertile males have shown that ORP negatively correlates with semen parameters, including sperm concentration and motility (Agarwal, Roychoudhury et al, ; Agarwal & Wang, ).…”
Section: Introductionmentioning
confidence: 99%